Evaluation of post-earthquake fire capacity of reinforced concrete elements - Vitorino, Hugo (2019)
Large earthquakes may cause a chain of events, and one of which can be fire after an earthquake. The effects of fire after earthquake on urban areas can be even worse than the effects of the earthquake itself. Buildings are not adequately designed for fire after an earthquake since most standards ignore that possibility. The aim of the work is to evaluate the consequences of the damage introduced due to the seismic events on the fire resistance of reinforced concrete elements. Several numerical analyses were performed to reinforce concrete elements using the program SAFIR, considering the thermal and mechanical analysis of the structure. The main variables in the analysis were the type of damage in the elements and the type of loads. The thermal analysis was performed using the standard fire curve ISO 834. The results show that the damage imposed by earthquake on reinforced concrete structures reduces the fire resistance, especially if the cover of the elements is removed and the reinforcement is exposed to fire.